THE IMPACT OF WCR CREATIVE THINKING SKILLS ON COGNITIVE LEARNING OUTCOMES OF JUNIOR HIGH SCHOOL STUDENTS - Maubuthy, Markus Simeon K.; Sukarjita, I Wayan; Jewaru, Aurelia Astria L.; Tefa, Maria (Program Studi Pendidikan IPA FKIP Universitas Jember, 2024)
This study investigates the impact of creative thinking skills, specifically through the Widening, Connecting, and Reorganizing (WCR) model, on the cognitive learning outcomes of junior high school students at SMPK Sint Vianney Soe. Creative thinking is recognized as a pivotal 21st-century competency that not only empowers students to devise innovative solutions but also influences their learning achievements. However, the relationship between creative thinking skills, particularly the WCR model, and cognitive learning outcomes has not been thoroughly explored. This research addresses this gap using a descriptive-correlational design, collecting data from 55 students through validated instruments. The findings revealed a significant relationship between creative thinking skills and cognitive learning outcomes, represented by the regression equation Y=26.354+0.691X. The analysis showed that 69.7% of the cognitive learning outcomes are influenced by creative thinking skills. Among the WCR dimensions, the widening aspect demonstrated the strongest correlation with cognitive outcomes, followed by the connecting aspect, while the reorganizing aspect was not significantly related to cognitive learning outcomes.